Guanxi and networking: The hidden business matrix of the Chinese economy - Markus Taube; Sven Horak (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2022)
China's economic structures, business dynamics and individual management decisions are not determined by the country's formal institutional arrangements alone. China's society, its politics and business are rather governed by powerful informal mechanisms that complement and sometimes overrule the ordering principles outlined in the formal sector. Network structures and guanxi, in particular, create hidden microcosms that exist beyond, or rather parallel to, markets and hierarchies and have a profound impact on the structures and dynamics of China's economy and its business sector. This phenomenon exists since the early days of China's civilisation and continues to shape the China of today (Bian, 2018; Fei, 1992; Yang, 1994). This contribution endeavours the following: (i) to outline the mechanics of guanxi relations and networks in Chinese society; (ii) to highlight the impact of guanxi relations and networks on Chinese business and management; and (iii) to discuss China's guanxi relations and networks in international comparison. In order to do so, this contribution integrates different streams of literature (economic and sociological network literature, management and organization studies, Chinese and East Asian area studies) into a comprehensive analysis shedding light on the various forms and dimensions in which guanxi relations and networks shape the way business is conducted in China.
Keywords: 330; Soziales Netzwerk; Unternehmensnetzwerk; Strategisches Management; Unternehmensorganisation; Unternehmenserfolg; China